Older PLHIV are at Higher Cardiovascular Risk with Poor Quality of Life - Shabil, Muhammed; Murti, Krishna; Kumar, V U.; Kumar, Rishikesh; Kumar, Nitesh; Dhingra, Sameer; Parihar, Vipan Kumar; Ravichandiran, V; Pandey, Krishna (Current HIV Research, 2023)
Background: People with HIV (PLHIV) face increased cardiovascular disease (CVD) risk due to inflammation and immune activation. Aging further amplifies this risk. Limited data exist on CVD risk in older PLHIV in India despite 2.14 million PLHIV with higher CVD risk factors.Methods: In a cross-sectional study in Bihar, India, 73 PLHIV and 30 control participants were enrolled. Demographics, social factors, clinical information, and CVD risk factors were collected. HbA1c levels and lipid profiles were analyzed, and 10-year CVD risk scores were calculated using the Framingham risk score (FRS) and Qrisk3. Quality of life (QoL) was assessed using WHOQOL- HIV-BREF.Results: Results showed higher LDL levels in non-HIV older participants and higher HDL levels in younger PLHIV participants. BMI differed significantly, with higher BMI in non-HIV older individuals and lower BMI in younger PLHIV individuals. Older PLHIV participants had significantly higher mean FRS and Q-Risk scores compared to older non-PLHIV and younger PLHIV groups. Among older PLHIV participants, six had higher CVD risk per FRS, while none in the other groups were classified as high CVD risk. Psychological, social relations and spirituality domains were highly deteriorated in older PLHIV, scoring 44.48, 42.72, and 41.2, respectively. The physical domain scored 57.6, and the environment scored 52.72 in the WHOQOL-HIV bref.Conclusion: In conclusion, older PLHIV in Bihar, India, face higher CVD risk compared to younger PLHIV and non-HIV individuals. FRS and Q-Risk scores effectively assessed CVD risk, identifying higher risk in older PLHIV. Age and BMI were significant predictors of high CVD risk. These findings emphasize CVD risk assessment and tailored management for older PLHIV. The QoL assessment findings indicate moderate deterioration in psychological, social relations, and spirituality domains among older PLHIV individuals. These results suggest greater challenges in psychological well-being, social interactions, and spirituality compared to the overall sample. Further research with larger samples and longitudinal designs is needed to confirm and extend these findings.
Keywords: Old age